2021
DOI: 10.1097/rlu.0000000000003511
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioblastoma

Abstract: Hemangioblastoma (HB) is the most common primary intra-axial posterior fossa tumor in adults and is a benign vascular neoplasm. We report the case of a 73-year-old man suffering from biochemical recurrence of prostate cancer where intense overexpression of prostate-specific membrane antigen (PSMA) was observed in HB in a PSMA PET/CT. Overexpression of PSMA in tumor-associated vascular structures has been proposed as an explanation of PSMA ligand uptake in several nonprostatic tumors. Given the pathological nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Patro et al reported a patient with an intracranial hemangiopericytoma in the posterior fossa, which demonstrated intense 68 Ga-PSMA-11 (HBED-CC) uptake and mild 18 F-FDG enhancement [80]. Gohimont et al reported a patient with a history of prostate cancer, who demonstrated 68 Ga-PSMA-HBED-CC uptake in the cerebellum on PET/CT, which was confirmed histopathologically as a hemangioblastoma [81].…”
Section: Other Cns Tumorsmentioning
confidence: 99%
“…Patro et al reported a patient with an intracranial hemangiopericytoma in the posterior fossa, which demonstrated intense 68 Ga-PSMA-11 (HBED-CC) uptake and mild 18 F-FDG enhancement [80]. Gohimont et al reported a patient with a history of prostate cancer, who demonstrated 68 Ga-PSMA-HBED-CC uptake in the cerebellum on PET/CT, which was confirmed histopathologically as a hemangioblastoma [81].…”
Section: Other Cns Tumorsmentioning
confidence: 99%
“…Hemangiopericytoma (HP) is rare cancer that occurs throughout the body, 1 with overexpression of PSMA, which can be a cause of pitfall in 68 Ga-PSMA-11 PET/CT. 2 The most common location of HP is in the pelvis and lower limbs, much less common in the head and neck region. 3 It is a mesenchymal neoplasm that derives from pericytes surrounding the capillaries.…”
mentioning
confidence: 99%